PENGARUH AUDIT TENURE DAN KUALITAS AUDIT TERHADAP AUDIT DELAY PADA SUB SEKTOR MINYAK MENTAH DAN GAS BUMI YANG TERDAFTAR DI BEI TAHUN 2017-2020 - Michael Josua Marbun; Remista Simbolon (Fakultas Ekonomi Universitas Advent Indonesia, 2021)
This study aims to examine audit tenure and audit quality in influencing audit delay in crude oil and gas sub-sector companies listed on the Indonesia Stock Exchange, using a period of 4 years (2017-2020). Observation data were 44 samples from 11 companies which were obtained using purposive sampling method. The analytical methods used are descriptive quantitative, normality test, multicollinearity test, heteroscedasticity test, autocorrelation test, partial, t test, multiple linear regression and F test. The results of the analysis of this study indicate that audit tenure has no significant effect on audit delay and audit quality has no significant effect on audit delay. The results of all the variables studied are that there is no significant effect between audit period and audit quality on audit delay in oil and gas sub-sector companies listed on the Indonesia Stock Exchange in 2017-2020.